Structures and functions of insect arylalkylamine N-acetyltransferase (iaaNAT); a key enzyme for physiological and behavioral switch in arthropods - Hiragaki, Susumu; Suzuki, Takeshi; Mohamed, Ahmed A. M.; Takeda, Makio (Frontiers in Physiology, 2015)
The evolution of N-acetyltransfeases (NATs) seems complex. Vertebrate arylalkylamine N-acetyltransferase (aaNAT) has been extensively studied since it Leads to the synthesis of melatonin, a multifunctional neurohormone prevalent in photoreceptor cells, and is known as as a chemical token of the night. Melatonin also serves as a scavenger for reactive oxygen species. This is also true with invertebrates. NAT therefore has distinct functional implications in circadian function, as timezymes (aaNAT), and also xenobiotic reactions (arylamine NAT or simply NAT). NATs belong to a broader enzyme group, the GCN5-related N-acetyltransferase superfamily. Due to low sequence homology and a seemingly fast rate of structural differentiation, the nomenclature for NATs can be confusing. The advent of bioinformatics, however, has helped to classify this group of enzymes; vertebrates have two distinct subgroups, the timezyme type and the xenobiotic type, which has a wider substrate range including imidazolamine, pharmacological drugs, environmental toxicants and even histone. Insect aaNAT (iaaNAT) form their own clade in the phylogeny, distinct from vertebrate aaNATs. Arthropods are unique, since the phylum has exoskeleton in which quinones derived from N-acetylated monoamines function in coupling chitin and arthropodins. Monoamine oxidase (MAO) activity is limited in insects, but NAT-mediated degradation prevails. However, unexpectedly iaaNAT occurs not only among arthropods but also among basal deuterostomia, and is therefore more apomorphic. Our analyses illustrate that iaaNATs has unique physiological roles but at the same time it plays a role in a timezyme function, at least in photoperiodism. Photoperiodism has been considered as a function of circadian system but the detailed molecular mechanism is not well understood. We propose a molecular hypothesis for photoperiodism in Antheraea pernyi based on the transcription regulation of NAT interlocked by the circadian system.